Design Science Research for Computational Thinking in Constructionist Education: A Pragmatist Perspective. - Dolgopolovas, Vladimiras; Dagienė, Valentina; Jasutė, Eglė; Jevsikova, Tatjana (Problems / Problemos, 2019)
The article examines the modern computer-based educational environment and the requirements of the possible cognitive interface that enables the learner's cognitive grounding by incorporating abductive reasoning into the educational process. Although the main emphasis is on cognitive and physiological aspects, the practical tools for enabling computational thinking in a modern constructionist educational environment are discussed. The presented analytical material and developed solutions are aimed at education with computers. However, the proposed solutions can be generalized in order to create a computer-free educational environment. The generalized paradigm here is pragmatism, considered as a philosophical assumption. By designing and creating a pragmatist educational environment, a common way of organizing computational thinking that enables constructionist educational solutions can be found.